2012
DOI: 10.1002/pros.22624
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine‐derived peptides promote prostate cancer cell survival through activation of IGF‐1R signaling

Abstract: Background Neuroendocrine (NE) cells promote the progression of prostate cancer to a castration-resistant state through the production of paracrine growth factors. We have demonstrated this principle using in vitro and in vivo proliferative endpoints; however, the contributions of NE-derived pro-survival factors and anti-apoptosis to this phenomenon have not been thoroughly investigated. Methods Here, we utilized conditioned-medium (CM) from LNCaP cells, engineered to undergo NE differentiation, and examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 48 publications
(86 reference statements)
1
36
0
1
Order By: Relevance
“…Experimental evidence has been presented showing that NE tumor cells can promote androgen-independent growth and tumorigenesis, 6 and invasion and metastasis of prostate cancer cells, 7 likely through their secreted products. 8,9 Studies over the years have shown that NE cells secret biogenic amines, neuropeptides and cytokines, while the bulk, non-NE tumor cells express receptors for many of the NE cell products.…”
Section: Neuroendocrine Cells In Benign Prostatementioning
confidence: 99%
“…Experimental evidence has been presented showing that NE tumor cells can promote androgen-independent growth and tumorigenesis, 6 and invasion and metastasis of prostate cancer cells, 7 likely through their secreted products. 8,9 Studies over the years have shown that NE cells secret biogenic amines, neuropeptides and cytokines, while the bulk, non-NE tumor cells express receptors for many of the NE cell products.…”
Section: Neuroendocrine Cells In Benign Prostatementioning
confidence: 99%
“…In androgen-dependent human prostate cancer LNCaP cells, the neuroendocrine-like differentiation is induced by an elevation of intracellular cAMP levels, androgen deprivation or treatment with interleukin-6 in a subpopulation of the cells [57] . The differentiated cells show androgen-independent properties, and secrete the proliferative neuropeptides such as neurotensin and parathyroid hormone-related peptide (PTHrP), which promote the proliferation of surrounding prostate cancer cells [58,59] . Ca v 3.2 T-type Ca 2+ channels are abundantly expressed in neuroendocrine-like differentiated LNCaP cells, and mediate Ca 2+ -dependent secretion [17,[60][61][62] , while the expression of L-type Ca 2+ channels is not detected in those cells [63] .…”
Section: The H 2 S/ca V 32 Pathway Regulates Neuroendocrine Secretiomentioning
confidence: 99%
“…В экспериментах с использованием линии клеток рака простаты PC3 показано, что ПТГрП способствует выживанию клеток рака ПЖ путем ак-тивации сигнализации инсулиноподобного факто-ра роста ИФР-1P. Селективный ингибитор ИФР-1P почти полностью блокировал выживание клеток рака простаты РС3 в присутствии доцетаксела [23].…”
unclassified